Peningkatan Pengetahuan dan Penerapan Teknologi Tepat Guna dalam Mengatasi Permasalahan Air Bersih - Karmini, Mimin; Ardiani Septiati, Yosephnia; Kahar, Kahar; Ruhmawati, Tati; Riyani, Ani; Bintan Zakiyah, Lutfia (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: Water is a very important need for human life. Physically, the water quality does not meet the requirements, namely: cloudy, yellow and smells of iron, chemically the Fe and Manganese levels do not meet the requirements, so clean water needs to be treated. The aim of community service is to increase knowledge, improve the quality of clean water physically and chemically, and increase the skills of the people of RW 12 and RW 13 regarding clean water processing. Method: Preparation, namely preparing counseling materials, making questionnaires, obtaining permits, coordinating with RT, RW, cadres, Pasirkaliki Community Health Center. Implementation Stage: for partners 1 and 2 respectively: conducting socialization, pretest, counseling, posttest, RT and RW deliberations, determining the location for installing clean water filters, and empowering the community when installing clean water filters. Result: 3 clean water filters have been installed in RW 12, namely the community well for 30 families, and 2 filter filters have been installed in private homes for 3-5 families in RW 13. 2 clean water filters have been installed in privately owned dug wells for 1- 3 families. There was an increase in the community's knowledge score regarding clean water processing in RW 12 by 37.47% and in RW 13 by 15.97%. Conclusion: 5 clean water filters have been installed in RW 12 and 13. There is a decrease in turbidity and dissolved Fe in the clean water.